Unsatisfactory glycemic control in type 2 Diabetes mellitus patients: predictive factors and negative clinical outcomes with the use of antidiabetic drugs (Brazilian Journal of Pharmaceutical Sciences, 2016)
Many factors can interfere with glycemic control in patients with type 2 diabetes mellitus and this patient group has an increased risk of experiencing drug-related negative outcomes (DNO). The aim of this study was to identify the predictive factors of unsatisfactory glycemic control and DNO in this group of patients. A cross-sectional study was conducted collecting data from prescriptions and interviews with 100 patients of the Endocrinology Clinic of the Hospital Complex of Sorocaba, São Paulo, Brazil. Variables associated with unsatisfactory glycemic control were determined and the DNO associated with antidiabetic drugs identified. Age (